Estrategias pedagógicas y su aporte en el aprendizaje de la conversión de un motor de carburador, a los estudiantes del tercero de bachillerato de la Unidad Educativa Milagro, del Cantón Milagro Provincia del Guayas - Gómez Aguirre, Olavides Ricardo (2019)
THEME: Pedagogical Strategies and their contribution in the learning of the conversion of a carburetor engine, to the students of the third year of high school of the Milagro Educational Unit, of the Canton Milagro province of Guayas AUTHOR: Olavides Ricardo Gómez Aguirre The present research work has as its main objective the pedagogical strategies that are used in class hours as learning tactics to raise the level of knowledge in students, as well as the use of methods and techniques, learning strategies play a role fundamental in education that will help us in the teaching process in the students by improving their thinking ability and ideas, in this way a pedagogical strategy of socio-economic entrepreneurship is developed in the students of the Milagro Educational Unit, applying the surveys to both students as teachers of the campus to achieve the following results in technical education, as stated at the beginning. Open in teachers a new area of thought and reflection in the updating of learning methods, therefore it will benefit students, teachers and society, because thus the mechanics of this sector of agriculture will be the best specialized and highly trained